2013
DOI: 10.1111/eci.12122
|View full text |Cite
|
Sign up to set email alerts
|

Portal vein omentin is increased in patients with liver cirrhosis but is not associated with complications of portal hypertension

Abstract: Current data show that PVS omentin is increased in liver cirrhosis but is not associated with complications of portal hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 36 publications
2
24
1
Order By: Relevance
“…Therefore, higher serum omentin levels in cirrhotic patients with increased IR is an unexpected finding. However, our results are in accordance with results obtained by Eisinger et al[19], who found omentin serum levels to be significantly decreased in cirrhotic patients with better insulin sensitivity.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Therefore, higher serum omentin levels in cirrhotic patients with increased IR is an unexpected finding. However, our results are in accordance with results obtained by Eisinger et al[19], who found omentin serum levels to be significantly decreased in cirrhotic patients with better insulin sensitivity.…”
Section: Discussionsupporting
confidence: 94%
“…Prothrombin is a key factor in clot formation, and elevated levels appear to promote venous thrombosis. In the study by Eisinger et al[19], omentin levels were significantly higher in the portal vein. In addition, these levels tended to be higher in the hepatic vein and systemic blood of patients with liver cirrhosis compared with the respective blood compartments of control patients with healthy livers.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Cirrhotic patients had higher portal vein omentin levels, which also were increased in systemic venous serum compared with controls, but there was no association with portal hypertension complications [43]. The main cause of cirrhosis in those patients was alcoholic hepatitis, with only three out of 34 having cirrhosis as a result of CHC.…”
Section: Discussionmentioning
confidence: 84%
“…During TIPS implantation, samples were obtained simultaneously of one of the hepatic veins (HVS) which was not drained by the TIPS-stent, of the portal vein (PVS) and of a peripheral vein such as the superior caval vein (SVS). Patient samples analyzed herein have been used in previous studies [23][24][25][26]. …”
Section: Transjugular Intrahepatic Portosystemic Shunt (Tips)mentioning
confidence: 99%